Estudo morfológico e molecular de larvas de diplostomoidea (trematoda: digenea) transmitidas por moluscos dulciaquícolas em Belo Horizonte, Minas Gerais, Brasil - Danimar Danilia López Hernández (2018)
The trematodes belonging to the superfamily Diplostomoidea parasitize, in the adult stage, birds, mammals and reptiles. These helminths have complex life cycles, involving gastropods and different groups of invertebrates and vertebrates as intermediate hosts. In Brazil, although more than 100 species were reported in vertebrates, including species with importance to pisciculture or potentially zoonotic, most of them present life cycle and transmitting molluscs unknown. In the present study, strigeid cercariae obtained in molluscs collected in aquatic collections from Belo Horizonte, Minas Gerais, Brazil, were submitted to morphological, experimental and molecular studies. The samples that were evaluated correspond to larvae previously collected (7 samples) and other obtained during malacological surveys carried out between May 2016 and May 2017 (4 samples). The amplification and sequencing of a partial region of 18S rRNA gene, the complete internal transcriptional spacer region (ITS), and a fragment of the gene cytochrome c oxidase I subunit (COI) were performed. The sequences obtained were compared with others available on GenBank . In addition, in order to obtain other developmental stages for taxonomic identification, the strigeid cercariae obtained during the new malacological collections were used to perform experimental infections of fish (Poecilia reticulata) and molluscs (Biomphalaria glabrata). In some cases, metacercariae obtained were used for the infection of birds (Gallus gallus domesticus) and mammals (Mus musculus). The use of the integrative taxonomy in the study of the strigeid cercariae evaluated allowed the identification of 6 species belonging to the superfamily Diplostomoidea. Among the members of the family Diplostomidae, two species, Austrodiplostomum compactum and Hysteromorpha sp., were found in Biomphalaria straminea. The nucleotide sequences obtained for the first species were similar to those available for isolates of the parasite from the USA, Brazil, Mexico and Peru. In relation to Hysteromorpha sp., although the morphology of cercariae and metacercariae obtained experimentally in P. reticulata, associated with the sequences obtained by nuclear markers, suggested coespecificity with Hysteromorpha triloba, significant differences were found between COI sequences of the samples from Brazil and isolates of H. triloba from Canada and Italy, suggesting the occurrence of cryptic species in this genus. Cercariae of Posthodiplostomum nanum were found in Gundlachia ticaga and metacercariae and one adult parasite were obtained experimentally in P. reticulata and mouse, respectively. The molecular and 10 phylogenetic data revealed that P. nanum groups with some species of the genus from North America and Europe, but the differences found are significant in relation to most of the cogeneric isolates. Three species belonging to the family Strigeidae were also found in B. straminea. Among these, cercariae of Cotylurus sp. presented sequences identical to those obtained for metacercariae of the type Tetracholyle found in B. straminea naturally infected. Another cercaria, identified as Apharyngostrigea sp., differs molecularly from congeneric species described from North America. Finally, a larva identified as Strigeidae gen. sp., for which experimental infection assays were unsuccessful, showed no significant similarity with sequences available for comparison. The results obtained revealed new associations between molluscs and trematodes of the superfamily Diplostomoidea in Brazil, resulting in a significant addition of nucleotide sequences to representatives of this group of trematodes.